Moral ambition : stop wasting your talent and start making a difference - Bregman, Rutger, 1988- (Little, Brown & Company, 2025)
"From the author of the New York Times bestsellers Humankind and Utopia for Realists--"a more politically radical Malcolm Gladwell" (The New York Times)--comes a bold manifesto daring us to harness our talents and transform our idealism into action, all with the goal of making the world a wildly better place."--Provided by publisher.